Oil and gas international year book - Financial Times; Financial Times (London : Longman Group, 1981)
Gave comprehensive information on oil and gas industries activities for the year 1981.It is an improvement in the earlier editions with addition of oil and gas more companies- those reporting revenues of at least one billion US dollar or equivalent and interim reports not included in earlier editions.
Include index
kjo 15/01/2019
Loans
Keywords: Petroleum industry and trade; Gas industry; Gas industry; Petroleum industry and trade; Aardolie; Aardgas